Event-related potential alterations in fragile X syndrome - Knoth, Inga Sophia; Lippe, Sarah (Frontiers in Human Neuroscience, 2012)
Fragile X Syndrome (FXS) is the most common form of X-linked intellectual disability, associated with a wide range of cognitive and behavioural impairments. FXS is caused by a trinucleotide repeat expansion in the FMR1 gene located on the X-chromosome. FMR1 is expected to prevent the expression of the “fragile X mental retardation protein (FMRP)”, which results in altered structural and functional development of the synapse, including a loss of synaptic plasticity. This review aims to unveil the contribution of electrophysiological signal studies for the understanding of the information processing impairments in FXS patients. We discuss relevant event-related potential (ERP) studies conducted with full mutation FXS patients and clinical populations sharing symptoms with FXS in a developmental perspective. Specific deviances found in FXS ERP profiles are described. Alterations are reported in N1, P2, Mismatch Negativity (MMN), N2 and P3 components in FXS compared to healthy controls. Particularly, deviances in N1 and P2 amplitude seem to be specific to FXS. The presented results suggest a cascade of impaired information processes that are in line with symptoms and anatomical findings in FXS.